2012
DOI: 10.1590/s1677-55382012000500008
|View full text |Cite
|
Sign up to set email alerts
|

Can we predict which patients will evolve to chronic kidney disease after nephrectomy for cortical renal tumors?

Abstract: ARTICLE INFO _________________________________________________________ ___________________Introduction: While some studies show that patients submitted to radical nephrectomy have a higher risk of developing chronic kidney disease (CKD), some studies report that carefully selected living kidney donors do not present a higher risk for CKD. Here, we aim to study predictive factors of CKD after radical nephrectomy. Materials and Methods: Between January 2006 to January 2010, 107 patients submitted to radical neph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 32 publications
(17 reference statements)
0
4
0
1
Order By: Relevance
“…CKD is an independent risk factor in chronic HF. Uninephrectomy induces renal dysfunction, especially under the high-salt condition, in animal models (2,38), although it is controversial whether uninephrectomy itself is at a risk factor for CKD in humans from the results of patients with cortical tumors (16,47). Although it is unclear in patients, in the mouse model of this study, uninephrectomy in the presence of hypertension and/or salt loading induced renal dysfunction, which is one of the key determinants in the development of HF in patients with hypertension (27).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CKD is an independent risk factor in chronic HF. Uninephrectomy induces renal dysfunction, especially under the high-salt condition, in animal models (2,38), although it is controversial whether uninephrectomy itself is at a risk factor for CKD in humans from the results of patients with cortical tumors (16,47). Although it is unclear in patients, in the mouse model of this study, uninephrectomy in the presence of hypertension and/or salt loading induced renal dysfunction, which is one of the key determinants in the development of HF in patients with hypertension (27).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that uninephrectomy induces renal dysfunction, especially under the high-salt condition, in animal models (2,38), although it is controversial whether uninephrectomy itself is generally a risk factor for CKD in humans (16,47). High salt intake is also associated with the occurrence of hypertension (7) and significantly increases the risk of total cardiovascular disease (44).…”
mentioning
confidence: 99%
“…In addition to the factors previously listed, hyperuricaemia and tumour size 4 cm have been associated with worse renal functional outcomes after tumour nephrectomy, with radical nephrectomy having a greater detrimental effect than partial nephrectomy. 6, [36][37][38][39][40][41] There are few studies assessing return to pre-operative levels of kidney function; however, in a study of 571 patients who underwent radical nephrectomy, Zabor and colleagues found that 44% and 58% of patients with an eGFR ! 60 and < 60 mL/min/ 1.73 m 2 respectively, returned to baseline levels of functioning after 24 months.…”
Section: Kidney Function After Nephrectomymentioning
confidence: 99%
“…Recently, several studies have evaluated the kidney and global outcomes of patients undergoing uninephrectomy [9][10][11]. Many have done so focusing on different surgical techniques that could preserve renal function, mainly partial nephrectomy [12][13][14].…”
Section: Introductionmentioning
confidence: 99%